Investigating the role of philosophy of mathematics as the bridge to meaningful mathematics teaching in the classroom - Ruttkamp-Bloem, Emma (University of Pretoria, 2024)
Dissertation (MPhil (Mathematics))--University of Pretoria, 2023.